Lipid Requirements for the Enzymatic Activity of MraY Translocases and in Vitro Reconstitution of the Lipid II Synthesis Pathway - Henrich, Erik (J Biol Chem, 2016)
Screening of new compounds directed against key protein targets must continually keep pace with emerging antibiotic resistances. Although periplasmic enzymes of bacterial cell wall biosynthesis have been among the first drug targets, compounds directed against the membrane-integrated catalysts are hardly available. A promising future target is the integral membrane protein MraY catalyzing the first membrane associated step within the cytoplasmic pathway of bacterial peptidoglycan biosynthesis. However, the expression of most MraY homologues in cellular expression systems is challenging and limits biochemical analysis. We report the efficient production of MraY homologues from various human pathogens by synthetic cell-free expression approaches and their subsequent characterization. MraY homologues originating from Bordetella pertussis, Helicobacter pylori, Chlamydia pneumoniae, Borrelia burgdorferi, and Escherichia coli as well as Bacillus subtilis were co-translationally solubilized using either detergent micelles or preformed nanodiscs assembled with defined membranes. All MraY enzymes originating from Gram-negative bacteria were sensitive to detergents and required nanodiscs containing negatively charged lipids for obtaining a stable and functionally folded conformation. In contrast, the Gram-positive B. subtilis MraY not only tolerates detergent but is also less specific for its lipid environment. The MraY·nanodisc complexes were able to reconstitute a complete in vitro lipid I and lipid II forming pipeline in combination with the cell-free expressed soluble enzymes MurA-F and with the membrane-associated protein MurG. As a proof of principle for future screening platforms, we demonstrate the inhibition of the in vitro lipid II biosynthesis with the specific inhibitors fosfomycin, feglymycin, and tunicamycin.